A Framework for Integrating Vernacular Architecture and Healing Environment Principles for Resilient Post-Disaster Housing - Ardiansyah, Ahmad Farid; Soetjipto , Jojok Widodo; Ratnaningsih , Anik (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2026)
Post-disaster housing is typically designed to meet immediate shelter needs, yet it often overlooks environmental adaptability, cultural continuity, and psychological recovery. This study proposes a multi-criteria framework by integrating principles of vernacular architecture and healing environments. A mixed-method approach was used, combining literature synthesis, criteria formulation, expert validation, and TOPSIS-based prioritization. Eight design criteria were assessed: ventilation, natural lighting, transitional spaces, building materials, cultural relevance, flexibility and resilience, sustainability, and psychological support. Expert judgment evaluated each criterion across two dimensions—vernacular and healing principles—followed by normalization, weighting, and ranking using TOPSIS. The results indicate that building materials achieved the highest performance score (Pi = 0.504), followed closely by transitional spaces (0.496), cultural relevance (0.495), and psychological support (0.491). However, the minimal variation between scores suggests that these criteria should not be treated as a strict hierarchy, but rather as an integrated design system. This framework offers a practical basis for developing post-disaster housing that is not only functional but also environmentally responsive, culturally sensitive, and supportive of occupant well-being.